1994
DOI: 10.4141/cjps94-082
|View full text |Cite
|
Sign up to set email alerts
|

Performance of inter-cultivar summer turnip rape hybrids in Saskatchewan

Abstract: pour le rendement grainier dans les croisements entre culiivars de Brassica rapa adapt€s aux conditions de production de l'Ouest ianadien est asrer iirpo.trnt pourjustifier la mise au point d'un systdme convenable de contr6le de la pollinisation pour la production de navette hybride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 6 publications
1
25
1
1
Order By: Relevance
“…The four cultivars selected for the formation of these synthetics are genetically different (Falk et al 1994), and therefore it was expected that they would be heterotic in crosses. The results of this study indicated that average synthetic and hybrid yields were equal (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The four cultivars selected for the formation of these synthetics are genetically different (Falk et al 1994), and therefore it was expected that they would be heterotic in crosses. The results of this study indicated that average synthetic and hybrid yields were equal (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Tobin and Sv8236580 are zero erucic acid, low glucosinolate, canola-quality cultivars. A detailed pedigree of each of the parents was given in a previous publication by Falk et al (1994).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations